MM-LoRa-Mod: A non-coherent LoRa modulation scheme for underwater acoustic communications - YU Xiao; XU Weikai; SUN Haixin; LIU Qi (Dianxin kexue)
LoRa (long-range) is an emerging low-power wide-area network technology. Facing challenges such as frequency selective fading multipath channels, existing LoRa schemes are subjected to issues like low data rates and high system complexity. To address these issues, a multi-mode LoRa (MM-LoRa-Mod) based modulation scheme was proposed. The frequency shifts of the multiple multiplexed chirp signals for information transmission were utilized in this scheme, thereby significantly enhancing data rates. Additionally, for underwater acoustic communication scenarios, a low-complexity non-coherent detection algorithm for MM-LoRa-Mod was introduced. Through the evaluation of MM-LoRa-Mod’s bit error rate performance in multipath channels, Watermark underwater acoustic channels, and shallow water acoustic channels, excellent anti-multipath fading and anti-Doppler frequency shift capabilities were demonstrated, indicating the high reliability of MM-LoRa-Mod in underwater acoustic communication scenarios.